Ethical issues in tissue engineering: a systematic review - Mohd. Azharuddin, Nur Syamimi; Ahmad Radzi, Muhammad Aa’zamuddin; Azhim, Azran; Sha'ban, Munirah; Abdulahi Hashi, Abdurezak (Malaysia Journal of Medicine and Health Science, UPM Press, 2022)
This study examines, classifies and discusses the ethical issues of tissue engineering published in selected online databases from the year 2015 to 2020. In overview, the published literature could be classified according to the type of ethical issues discussed, the phase in development in which the ethical issues are prominently existing and into the type of journal they are published. It proceeds with in-depth discussions on selected relevant issues that deemed to be needing further attention and clarification. It will give the readers a broad mapping of ethical issues currently existing and discussed in the context of tissue engineering and highlights the conventional responses on the issues.